The Strategi Pondok Pesantren Darussa’adah Muara Enim Dalam Meningkatkan Jumlah Santri - Nurhaliza; Candra Darmawan (Social Science and Contemporary Issues Journal, 2023)
ABSTRACT: This research is entitled "Strategy of the Darussa'adah Muara Enim Islamic Boarding School in Increasing the Number of Santri". The aim of this research is to find out the strategy of the Darussa'adah Muara Enim Islamic Boarding School in increasing the number of students. research taken by the author of this study using qualitative research methods. The results of the research (1) Holding a Festival or Competition. It is hoped that the competition activities carried out with Islamic nuances will become a place to meet other schools and by holding this festival it is hoped that it will have a positive impact on Madrasah aliyah Darussa'adah and be able to introduce Madrasah Aliyah to the community. Direct Promotion: a) Visiting junior high schools: This socialization aims to be able to provide information to students regarding the Madrasah Aliyah program and to introduce Madrasah Aliyah Darussa'adah to the wider community. b) Promotion through parents and through alumni: word-of-mouth promotion carried out by santri guardians to the wider community has a very good impact in increasing the amount of community interest, especially if they feel satisfaction with the education their children get while studying there. Promotion through alumni is very influential on people's assessment of changes in themselves, especially when they have achievements and become children who have a positive impact. (1) Improving Madrasah Excellence: (a) Developing extracurriculars: Extracurriculars become a vehicle for developing the potential of students, and it is hoped that Madrasah aliyah Darussa'adah can develop the talents/abilities that exist in each Santri/student. (2) Improving the quality of students. Improving the quality of students must be balanced with teacher professionalism and developing the potential of students according to the talents and interests of the students themselves. (3) Improve facilities and infrastructure. The facilities and infrastructure at Madrasah Aliyah Darussa'adah are quite complete, although there are still things that need to be completed. a) Through print media: Promotion of print media includes brochures and banners, brochures and banners are used as promotional material for Madrasah Aliyah Darussa'adah to attract new students so that they can increase the number of students and are considered simpler and easier to reach the community. b) Through social media: Electronic media promotion is one of the most effective promotions to use because it allows the public to easily find information on Madrasah Aliyah Darussa'adah through social media such as Facebook and the YouTube channel. KEYWORDS: Strategy, Muara Enim Darussa'adah Islamic Boarding School, Number of Santri.